Hubungan antara Hardiness dengan Psychological Well-Being pada Korban Bullying di SMA X Klaten - Maliqazuhra Iqbal; Amin Al Adib; Ria Rizkiyana (Pusat Riset dan Inovasi Nasional, 2024)
Hardiness is one of the factors that can support the psychological well-being of individuals, especially for adolescents who experience bullying. This study aims to empirically examine the relationship between hardiness and psychological well-being in victims of bullying at SMA X Klaten. The population in this study was 165 students, while the study subjects amounted to 60 students who were victims of bullying, selected using purposive sampling techniques. Data collection was carried out using two measuring tools, namely the Psychological Well-Being scale (α = 0.910) and the Hardiness scale (α = 0.785). The data was analyzed using the Pearson Product Moment correlation technique. The results of the analysis showed a correlation coefficient value of rxy = 0.738 (p < 0.05) which indicated a positive and significant relationship between hardiness and psychological well-being. Thus, the higher the level of hardiness that an individual has, the higher the level of psychological well-being, and vice versa. These findings confirm that psychological well-being in bullying victims can improve if the victim is a resilient person. In addition, this study provides an overview that efforts to strengthen character and self-resilience through psychological interventions and school environment support can be an important strategy in helping bullying victims achieve better psychological well-being.